A distributed consensus-based optimal energy management approach in DC microgrids. (September 2022) - Zhang, Jingqiu; She, Buxin; Peng, Jimmy Chih-Hsien; Li, Fangxing
Abstract: A distributed economical coordinator is presented to maximize the social welfare for distributed generations, storage units, and consumers within a DC microgrid. This is realized through a two-layer control framework, which only requires information exchange among neighboring units. The economical coordination is then established using a consensus-based algorithm for computing the economical correction terms among the participants. Furthermore, power sharing among the distributed generations is achieved using a modified droop controller. The control parameters are determined based on the mathematical analysis of the two-layer control framework, ensuring the optimal power sharing among all participants. Finally, numerical case studies demonstrate the effectiveness of the proposed framework. Highlights: Proposed a consensus-based optimization approach to maximize the social welfare in a DC microgrid. Proposed a two-layer control framework to achieve real-time optimal power sharing. Demonstrated the superiority of the proposed approach from the perspective of number of required iterations.